Economywide impact of maize export bans on agricultural growth and household welfare in Tanzania: A Dynamic Computable General Equilibrium Model Analysis - Diao, Xinshen; Kennedy, Adam; Mabiso, Athur; Pradesha, Angga (International Food Policy Research Institute, 2013)
We study the impact of export bans in Tanzania using a computable general equilibrium model. We find that although maize is an important food crop in Tanzania, its contribution to food price inflation is rather limited, and that banning cross-border maize exports lowers the national food price index by only 0.6-2.4 percent compared with the free-export scenario. The benefits of lower prices are captured primarily by urban households, but maize producer prices decrease by 7-26 percent, depending on the region. We also find that the export ban decreases the wage rate for low-skilled labor and the returns to land, while returns to nonagricultural capital and wage rate for the skilled labor increase, further hurting poor rural households and thus increasing poverty for the country as a whole.